التعليم الابداعي ....اليابان نموذجا - الكرد, انتصار (Sciences de l'Homme et de la Société, 2014)
هدفت  الدراسة  إلى  معرفة كيف  نجحت  اليابان  في  تطوير النظام التعليمي وجعله  تعليمًا إبداعيًا، وهذا طبعًا  لم  يتأتى إلا عن طريق  توفير وتقديم خطة  أو استيراتيجية  واضحة، وكما أشارت الدراسة إلى تبيان أهم وأسس الآليات النظرية المستخدمة في صيرورة خطة واستراتيجية التطوير التعليمية اليابانية. وقد حاولنا من خلال هذه الدراسة – النظرية - تحليل أهم  مراحل تطور التعليم  عامةً والتعليم الإبداعي في اليابان خاصةً.     The study aims to find out how Japan has succeeded in the development of the educational system and make educated creative, and of course, this did not come only through the provision and submit a plan or clear strategy. The study showed the most important mechanisms used in the process of strategy development of learning in Japan. We have tried through this theoretical study analysis of the most important stages of the development of education in general and creative education, especially in Japan.